THE RELATIONSHIP BETWEEN LEARNING DISCIPLINE, INTERESTS OF LEARNING AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOME OF STUDENTS SMP NEGERI 15 YOGYAKARTA - Budi Prabowo; Abdul Taram (Universitas Ahmad Dahlan, 2017)
Low mathematics learning outcomes are thought to be related to several factors. These factors include learning discipline, interest in learning and learning environment at home. This study aims to determine the presence or absence of a positive and significant relationship between learning discipline, learning interest and learning environment at home with mathematics learning outcomes for students of class VIII of SMP Negeri 15 Yogyakarta in 2015/2016 Academic Year. The population in this study were all regular students of class VIII in the even semester of SMP Negeri 15 Yogyakarta with 5 classes. A sample of 1 class with 27 students was taken by cluster random sampling technique obtained by class VIII B as a research class. Data collection techniques using a questionnaire method to determine the discipline of learning, interest in learning and learning environment at home students, and test methods to determine student learning outcomes in mathematics. To test the instrument using a validity test, reliability testing and distinguishing power test. After the data is collected, an analysis prerequisite test is conducted which includes a normality test, an independence test, and a linearity test. Data analysis for hypothesis testing uses product-moment correlation analysis, multiple linear regression analysis for 2 variables and multiple regression analysis for 3 variables. The results showed there was a positive and significant relationship between learning discipline, learning interest and learning environment at home with mathematics learning outcomes, with Y Ì‚= -193,541 + 1,465X_1+ 1,047X_2+0,35X_3. Relative contribution X1 = 58,95661%, X2 = 34,39229% dan X3 = 6,651091% and effective donations X1 = 39,94658%, X2 = 23,30281% dan X3 = 4,506506%.